Pharmacosurveillance in phonoaudiological rehabilitation of patients with neurological illnesses - da Silva, Ana Paula; Ladislau de Araújo, Jéssica; Chaves de Souza, Verônica; Ochi Takiuti, Viviane; Macedo Silva, Alexsandro; Paiva Farias, Luciana; de Jesus Gonçalves, Maria; Hey Tocci Salcedo, Priscilla (O Mundo da Saúde, 2008)
Patients with neurological illness can present alterations of speech, language and functions related to feeding, besides physical and/or psychic limitations, due to disturbances of the central or peripheral nervous system. Medications used in the pharmacological treatment of these patients can potentiate dysfunctions already present due to their possible side-effects, which can worsen the clinical condition of patients and as a consequence, the process of phonoaudiological rehabilitation. The aim of this work is to identify medicine side-effects (MSE) of the main drugs given to patients with neurological illnesses and the degree of interference of these in phonoaudiological therapy. For the phonoaudiologist, the knowledge of the effect of MSE is essential, as well as having information about the degree of interference these drugs have on communication and feeding functions. Thus, the practice of pharmacosurveillance helps phonoaudiologists prevent problems related to drugs, guaranteeing therapeutic evolution, rehabilitation and the improvement of the patient’s quality of life.